2023
DOI: 10.1111/iju.15188
|View full text |Cite
|
Sign up to set email alerts
|

Fusion‐targeted biopsy significantly improves prostate cancer detection in biopsy‐naïve men

Abstract: Objective The precise diagnosis of prostate cancer (PC) is crucial to avoid underdiagnosis, overdiagnosis, and overtreatment. We aimed to compare clinically significant PC (csPC) detection between MRI/ultrasound fusion‐targeted prostate (TBx) compared to systematic biopsy (SBx) in biopsy‐naïve Japanese men. Methods We included patients with suspect PC due to elevated PSA level or abnormal digital rectal examination, or both. csPC was defined as International Society Urological Pathology (ISUP) grade group ≥2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…These biomarkers can obviate the need for unnecessary biopsies in patients with highest PI‐RADS category ≤3. In the present study, the combination of target and systematic biopsy has shown to improve csPC detection 3 . Although csPC detection based on MRI has been established and developed, the removal of systematic biopsy has still not been recommended for the detection of MRI‐invisible csPC.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…These biomarkers can obviate the need for unnecessary biopsies in patients with highest PI‐RADS category ≤3. In the present study, the combination of target and systematic biopsy has shown to improve csPC detection 3 . Although csPC detection based on MRI has been established and developed, the removal of systematic biopsy has still not been recommended for the detection of MRI‐invisible csPC.…”
mentioning
confidence: 83%
“…Another study reported that, compared with systematic biopsy, csPC detection in the target biopsy was significantly higher 3 . Furthermore, csPC detection from a target biopsy for the region with Prostate Imaging Reporting and Data System (PI‐RADS) category ≤3 was found to be low 3 .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Local recurrence was diagnosed using transperineal systematic biopsy with MRI/ultrasound fusion-targeted prostate (TRINITY; Koelis, Grenoble, France). 10 Pathological diagnosis was performed by several institutional pathologists. The time to recurrence was defined as the duration from the date of initial diagnosis by biopsy to the date of local recurrence detected by biopsy.…”
Section: Treatment and Clinical Data Collectionmentioning
confidence: 99%
“…Blas et al 1 . reported that magnetic resonance imaging (MRI)/ultrasound fusion‐targeted biopsy (MRI‐TBx) significantly outperformed 12‐core standard transrectal ultrasonography‐guided systematic biopsy (SBx) in terms of detecting clinically significant prostate cancer (csPC) and decreasing non‐csPC detection in biopsy‐naive men.…”
mentioning
confidence: 99%